ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN INDUSTRI KECIL DI KOTA PADANGSIDIMPUAN DAN KABUPATEN TAPANULI SELATAN - Ali Hardana (Institut Agama Islam Negeri Padangsidimpuan, 2018)
Industrialization is a basic tool for national development and regional development, especially for small industrial business activities that are important in order to realize a just and prosperous society. To achieve this, the government made a policy to increase small industry revenues. The main objective of this research is to find out the number of small business loans (X1), the number of small-scale industrial workers (X2), economic growth (X3), and the number of small-scale industries (X4), significantly affecting Small-Scale Industrial Revenues in Padangsidimpuan City (Y1) and South Tapanuli Regency (Y2). In this study the data used is secondary data obtained from the Central Bureau of Statistics of Padangsidimpuan for 15 years starting from 2002-2016. The data were analyzed using multiple linear regression models, namely an analysis to determine each of the independent variables (X) to the bound variable (Y) both silmultanally and partially. Based on the results of the analysis and testing the hypothesis obtained results of Fcount of 18,900 Ftable = 3,48 for the City of Padangsidimpuan and for the District of South Tapanuli obtained the results of Fcount 3.616 Ftable = 3,48 which means simultaneously the four independent variables have a real influence on industrial income small in Padangsidimpuan City and South Tapanuli Regency. Partial testing of the city of Padangsidimpuan obtained tcount for the variable X1 of 7.367 t-table of 2.228 means that the variable X1 can contribute to the real effect on the dependent variable Y1. Partial testing of South Tapanuli Regency obtained tcount for variable X2 of 3.160 t-table of 2.228 means that variable X2 can contribute to the real influence on the dependent variable Y2, for variable X4, t-count of 2.986 t-table of 2.228 means that variable X4 can contribute to the real influence against the dependent variable Y2